Antiviral drugs prioritization for COVID-19 management based on rational selection - Joshi, Rakesh S.; Giri, Ashok P.; Kulkarni, Mahesh J.; Gupta, Mahesh; Verma, Savita; Chaudhry, Dhruva; Deshmukh, Narendra; Chugh, Anita (Current Science, 2021)
The SARS-CoV-2 infection has resulted in COVID-19 pandemic worldwide. It has infected around 0.1 billion individuals and caused 2 million fatalities across the globe till mid-January 2021. Drug repurposing has been utilized as the most preferred therapeutic intervention for COVID-19 mitigation due to its necessity and feasibility. To prioritize therapeutic regime against COVID-19, we used 61 antiviral drugs and their combinations. Selected molecules were subjected to virtual screening against: (i) human angiotensin-converting enzyme 2 receptor binding domain (hACE-2) which serves as an anchor for virus attachment and entry, (ii) SARS-CoV-2 RNA dependent RNA polymerase (RdRp) responsible for viral RNA replication, and (iii) SARS-CoV-2 main protease (M-Pro) needed for viral polyprotein slab proteolytic processing. Based on docking score, pharmacodynamic and pharmacokinetic parameters, combinations of Daclatasvir, Elbasvir, Indinavir, Ledipasvir, Paritaprevir and Rilpivirine were analysed further. Our analysis suggested Sofosbuvir in combination with Ledipasvir and Daclatasvir as potential therapeutic agents for SARS-CoV-2. The combined score suggests that these combinations have superior anti-SARS-CoV-2 potential than Remdesivir and other investigational drugs. The present work provides a rationale-based approach to select drugs with possible anti-SARS-CoV-2 activity for further clinical evaluation.
Keywords: Drug repurposing; hACE-2; main protease; RNA dependent RNA polymerase; SARS-CoV-2

Silk fibroin microparticle scaffold for use in bone void filling: safety and efficacy studies - Deshpande, Rucha; Shukla, Swati; Kale, Amod; Deshmukh, Narendra; Nisal, Anuya; Venugopalan, Premnath (ACS Biomaterials Science & Engineering, 2022)
Silk fibroin (SF) is a natural biocompatible protein polymer extracted from cocoons of silkworm Bombyx mori. SF can be processed into a variety of different forms and shapes that can be used as scaffolds to support bone regeneration. Threedimensional (3D) SF scaffolds have shown promise in bone-void -filling applications. In in vitro studies, it has been demonstrated that a microparticle-based SF (M-RSF) scaffold promotes the differentiation of stem cells into an osteoblastic lineage. The expression of differentiation markers was also significantly higher for M-RSF scaffolds as compared to other SF scaffolds and commercial ceramic scaffolds. In this work, we have evaluated the in vitro and in vivo biocompatibility of M-RSF scaffolds as per the ISO 10993 guidelines in a Good Laboratory Practice (GLP)-certified facility. The cytotoxicity, immunogenicity, genotoxicity, systemic toxicity, and implantation studies confirmed that the M-RSF scaffold is biocompatible. Further, the performance of the MRSF scaffold to support bone formation was evaluated in in vivo bone implantation studies in a rabbit model. Calcium sulfate (CaSO4) scaffolds were chosen as reference material for this study as they are one of the preferred materials for bone-void -filling applications. M-RSF scaffold implantation sites showed a higher number of osteoblast and osteoclast cells as compared to CaSO4 implantation sites indicating active bone remodeling. The number density of osteocytes was double for M-RSF scaffold implantation sites, and these M-RSF scaffold implantation sites were characterized by enhanced collagen deposition, pointing toward a finer quality of the new bone formed. Moreover, the M-RSF scaffold implantation sites had a negligible incidence of secondary fractures as compared to the CaSO4 implantation sites (similar to 50% sites with secondary fracture), implying a reduction in postsurgical complications. Thus, the study demonstrates that the M-RSF scaffold is nontoxic for bone-void -filling applications and facilitates superior healing of fracture defects as compared to commercial calcium-based bone void fillers.
Keywords: Biocompatibility; biological safety; bone void filler; ISO 10993; M-RSF; Serioss; Silk fibroin

Comprehensive molecular and clinical investigation of approved Anti-HCV drugs repurposing against SARS-CoV-2 infection: a glaring gap between benchside and bedside medicine - Bansode, Sneha; Singh, Pawan Kumar; Tellis, Meenakshi; Chugh, Anita; Deshmukh, Narendra; Gupta, Mahesh; Verma, Savita; Giri, Ashok; Kulkarni, Mahesh; Joshi, Rakesh; Chaudhary, Dhruva (Vaccines, 2023)
The limited availability of effective treatment against SARS-CoV-2 infection is a major challenge in managing COVID-19. This scenario has augmented the need for repurposing anti-virals for COVID-19 mitigation. In this report, the anti-SARS-CoV-2 potential of anti-HCV drugs such as daclatasvir (DCV) or ledipasvir (LDP) in combination with sofosbuvir (SOF) was evaluated. The binding mode and higher affinity of these molecules with RNA-dependent-RNA-polymerase of SARS-CoV-2 were apparent by computational analysis. In vitro anti-SARS-CoV-2 activity depicted that SOF/DCV and SOF/LDP combination has IC50 of 1.8 and 2.0 mu M, respectively, comparable to remdesivir, an approved drug for COVID-19. Furthermore, the clinical trial was conducted in 183 mild COVID-19 patients for 14 days to check the efficacy and safety of SOF/DCV and SOF/LDP compared to standard of care (SOC) in a parallel-group, hybrid, individually randomized, controlled clinical study. The primary outcomes of the study suggested no significant difference in negativity after 3, 7 and 14 days in both treatments. None of the patients displayed any worsening in the disease severity, and no mortality was observed in the study. Although, the post hoc exploratory analysis indicated significant normalization of the pulse rate showed in SOF/DCV and SOF/LDP treatment vs. SOC. The current study highlights the limitations of bench side models in predicting the clinical efficacy of drugs that are planned for repurposing.
Keywords: antiviral; COVID-19; daclatasvir; ledipasvir; SARS-CoV-2; sofosbuvir

Engineered silk matrix as a substitute for acellular dermal matrix in breast reconstruction surgery - Deshpande, Rucha; Shukla, Swati; Kale, Amod; Sayyad, Raeesa; Kewale, Bhawana; Deshmukh, Narendra; Nisal, Anuya; Venugopalan, Premnath (International Journal of Biological Macromolecules, 2025)
Implant-based breast reconstruction is a common standard of care for breast cancer patients following mastectomy. To support implant weight and placement, surgeons utilize autologous tissues, acellular dermal matrices (ADMs), or synthetic meshes. While ADMs provide structural support, they present significant risks, including infection transmission and seroma. Conversely, synthetic meshes exhibit poor cellular adhesion, leading to inadequate tissue integration. To address these challenges, there is a need for a matrix that enhances tissue integration while minimizing infection risks and other complications. Silk fibroin (SF), a natural biopolymer, possesses excellent biocompatibility and mechanical properties. This study introduces a novel engineered silk matrix (ESM) as an advanced solution for soft tissue regeneration, specifically in breast reconstruction surgery. The present study establishes the safety of ESM and evaluates its potential a tissue regeneration matrix through extensive in-vitro and in-vivo analyses. In-vitro assays demonstrated superior cellular adhesion, proliferation of human mammary fibroblast cells (HMFCs), collagen deposition and angiogenesis in ESM compared to collagen matrices and ADMs. Safety assessments, conducted in accordance with ISO 10993 guidelines, confirmed noncytotoxic nature of ESM. Furthermore, subcutaneous implantation revealed no systemic toxicity or adverse tissue reactions. In-vivo studies utilizing a Yorkshire pig model of simulated breast reconstruction surgery, demonstrated superior performance of ESM over collagen matrices in tissue regeneration. The findings showed enhanced fibroblast density, increased collagen deposition, and improved vascularization. These results suggest that ESM is a safer and more effective alternative to ADMs in breast reconstruction, with the potential to revolutionize post-mastectomy care for breast cancer patients.
Keywords: Biocompatibility; Breast reconstruction; ISO 10993; Polymer; Safety; Silk protein; tissue regeneration